Perfluorinated graded-index plastic optical fiber bragg gratings: observation and theoretical analysis of unique dependence on pressure - Ishikawa, Ryo; Lee, Heeyoung; Lacraz, Amédéé; Theodosiou, Antreas; Kalli, Kyriacos; Mizuno, Yosuke; Nakamura, Kentaro (My University, 2017)
The pressure dependence of a fiber Bragg grating (FBG) inscribed in a perfluorinated graded-index plastic optical fiber (POF) is investigated at 1550 nm. As pressure is applied, the Bragg wavelength shifts with a relatively long time constant (several tens of minutes) with a coefficient of 1.3 nm/MPa, which is over 5 times the highest value previously reported in other POF-FBGs). After the Bragg wavelength becomes constant at 0.5 MPa, the pressure-dependence coefficient is quickly measured to be -0.13 nm/MPa, the sign of which is opposite to those of other POF-FBGs. These unique behaviors are theoretically analyzed.
Keywords: Fiber Bragg gratings; Fiber optic sensors; Optical fibers; Bragg wavelength; Plastic optical fibers; Graded index plastic optical fiber